2016
DOI: 10.3329/bmrcb.v41i3.29886
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic and antidepressant activities of Brassica rapa subspecies chinensis (L.) Hanelt on Swiss-albino mice model

Abstract: Bangladesh being a subtropical country provides varieties of herbs and vegetables. Brassica is a broad genus available in Bangladesh and it encompasses a lot of nutritive herbs. Among these, Brassica rapa subspecies chinensis (L.) Hanelt (Family-Brassicaceae) is popular in many parts of the world. In the quest of medicinal property, this plant was investigated here for observing analgesic and antidepressant activities in Swiss-albino mice model. The herb was extracted well with methanol and then assayed by ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…italica sprouts might involve opioid mechanisms (Baenas et al 2017 ). Our results support central analgesic-like effects in other Brassica species since it was reported that an extract of Brassica rapa subspecies chinensis extract increased withdrawal latency in the tail immersion test (Rahman et al 2015 ). Preliminary studies have already reported the analgesic-like response of the pure compound SFN in neuropathic (Wang and Wang 2017 ) and abdominal (Guadarrama-Enriquez et al 2018 ) pain, and for the sprouts (Baenas et al 2017 ), which effects were avoided in the presence of an opioid antagonist reinforcing the involvement of this inhibitory neurotransmission.…”
Section: Discussionsupporting
confidence: 90%
“…italica sprouts might involve opioid mechanisms (Baenas et al 2017 ). Our results support central analgesic-like effects in other Brassica species since it was reported that an extract of Brassica rapa subspecies chinensis extract increased withdrawal latency in the tail immersion test (Rahman et al 2015 ). Preliminary studies have already reported the analgesic-like response of the pure compound SFN in neuropathic (Wang and Wang 2017 ) and abdominal (Guadarrama-Enriquez et al 2018 ) pain, and for the sprouts (Baenas et al 2017 ), which effects were avoided in the presence of an opioid antagonist reinforcing the involvement of this inhibitory neurotransmission.…”
Section: Discussionsupporting
confidence: 90%
“…The utilized doses of BRFE were based on previous biological investigations for the same species using different plant organs. 29 , 30 …”
Section: Methodsmentioning
confidence: 99%
“…Anti-depressant assay: The crude methanolic extract of B. verrucosa was subjected for the evaluation of antidepressant assay through phenobarbitone-Na induced sleeping time test (Rahman et al, 2015). Here, the test groups were orally administered with test samples prepared with normal saline water and Tween-80 at doses of 200and 400-mg/kg b.w., while the positive control group was treated with diazepam (1 mg/kg b.w.)…”
Section: Methodsmentioning
confidence: 99%